Mapping soil and pasture variability with an electromagnetic induction sensor - Serrano, João M. (2012)
The general objective of this study was to test a non-contact electromagnetic induction probe to evaluate the soil and pasture variability in a precision agriculture project. Assessment of the variability of soil and vegetation in a permanent pasture is the basis for management of variable rate fertilization, which is the main instrument used by farmers for improvements in permanent pasture in Alentejo, Portugal. The traditional process of sampling and evaluation of the soil is very demanding in terms of time, labour and reagents, and can derail a project of precision agriculture. This paper describes the major steps followed by the authors to simplify the methodology of soil evaluation in a permanent pasture based on measuring the apparent soil electrical conductivity. Tests were carried out in a parcel of approximately 6 ha, which was subdivided into 28 m × 28 m squares. The soil samples and the evaluation of apparent electrical conductivity were geo-referenced with a global positioning system. The geospatial data were processed by ArcGIS software and the statistical analysis resulted in significant correlation coefficient values between apparent electrical conductivity and altitude, soil pH and pasture dry matter yield.